Prostaglandin E Receptor EP4 expression, survival and pattern of recurrence in locally advanced NSCLC. (November 2016) - Bhooshan, Neha; Staats, Paul N.; Fulton, Amy M.; Feliciano, Josephine L.; Edelman, Martin J.
Abstract: Background: Elevated COX-2 expression has been correlated with inferior outcome in NSCLC. COX-2 catalyzes the transformation of arachidonate to PGE2 . We and others have demonstrated that PGE2 induces proliferation and metastatic spread and immunosuppression through the G protein-coupled EP4 receptor. We hypothesized that EP4 expression on malignant cells would correlate with outcome and patterns of relapse after treatment of LANSCLC stage IIIA (7th edition, N2+). Methods: Tissue specimens from 41 pts treated for LANSC at UMGCC were obtained. A tissue microarray was prepared and examined for EP4 expression. Intensity of staining was scored semi-quantitatively as 0–4 in both the nuclear and cytoplasmic compartments by a pathologist blinded to the clinical data. Results: EP4 nuclear staining 0–1 vs. 2+ was associated with overall survival, (OS) (44.3 vs. 18 mo; HR = 0.41, p = 0.024) and numerically superior progression free survival (PFS) (16.4 vs. 10.2 mo, p =0.16). EP4 cytoplasmic staining did not correlate with OS (0–1 vs. 2+, 23.8 vs. 28.8 mo; HR = 1.2, p = 0.81). Relapse pattern (no relapse or local vs. systemic) did not correlate with EP nuclear staining (p = 1.0, X 2 ). Conclusions: This is the first clinical study of EP4 expression in lung cancer. There was a significant correlation between OS and nuclear EP4 expression, indicating that this is a potential therapeutic target. Studies with AT-007, a specific inhibitor of EP4, are planned to commence this year.